A novel LC-MS/MS method for the simultaneous analysis of selected fat-soluble vitamins in serum obtained from pediatric patients with pneumonia. Issue 25 (15th June 2022) - Zhang, Min; Huang, XiaoLan; Song, MeiYan; Mi, Lala; Yin, Yan; Wang, Fang; Chen, Min; Zhang, Ting; Yang, Jian; Cui, XiaoDai
Abstract : The simultaneous quantification of selected fat-soluble vitamins in serum from pediatric pneumonia patients was carried out using a LC-MS/MS method. Abstract : Several observational studies have reported associations between low levels of fat-soluble vitamins (A, D and E) and the incidence of pneumonia. Whether infection affects or negatively regulates serum vitamin levels remains controversial. Our aims were to develop and validate a simple-pretreatment and fast method to determine the serum levels of selected fat-soluble vitamins, namely vitamin A (retinol), vitamin D (25-OH-D3, 25-OH-D2, and 3-epi-25-OH-D3 ), and vitamin E (α-tocopherol), in children suffering from pneumonia during the acute phase and after inflammatory marker recovery. The sample preparation procedure involving protein precipitation and filtration was finished in one step, and separation took 8 min per sample. The calibrations were linear, with R 2 > 0.99. Both the intra-run ( n = 6) and inter-run ( n = 3) precision (relative standard deviation, RSD%) values were below 14.61%. The spiked recoveries at 3 concentrations ranged from 80.97 to 111.91%. Accuracies were calibrated using both National Institute of Standards and Technology serum (NIST 968f) and external quality assurance (EQA) samples offered by the National Center of Clinical Laboratories of China, and the relative error (RE%) values ranged from −13.17% to 12.53%. Clinical sample analysis revealed that infection did alter the serum retinol concentration and it did not alter the 25-OH-D and α-tocopherol levels in young children with pneumonia.